Synthesis, characterization, and biological properties of nickel (II) complexes with derivatives of testosterone thiosemicarbazone - Heng, Mok Piew (2015)
The side effects of cisplatin such as toxicities are mainly due to the lack of selectivity of this chemotherapeutic agent. In order to increase selectivity of an anticancer agent, hormone molecule that targets a specific receptor may be utilized. The notorious side effects of cisplatin and the potential of hormone molecule have generated a research problem: can a cytotoxic compound with better selectivity and/or specificity made of ligand containing a hormone molecule be prepared? The aim of this study is to prepare cytotoxic nickel complexes containing Schiff base ligands of testosterone and thiosemicarbazide, which are selective towards cancerous cells. Besides, their ability as DNA binders and topoisomerase I inhibitors were tested as well. Three Schiff base ligands that are made of testosterone and three derivatives of thiosemicarbazide (TT, TE, and TP) and their nickel (II) complexes (NT, NE, and NP) were synthesized. Characterizations of these compounds were done by means of FTIR, CHN, 1H-NMR, and X-ray crystallography. Mononuclear complexes NT, NE, and NP adopt the distorted square planar geometry, with two molecules of Schiff base ligand were coordinated to nickel ion via two imine nitrogens and two tautomericthiol sulfurs. The cytotoxicity of these compounds against several cancerous cell lines (prostate cancer cells PC-3 and LNCaP, and colon cancer cell HCT 116) was investigated via MTT assay, with cisplatin as positive reference standard. Preferences towards different cancer cell lines were shown, where parent ligands and their nickel complexes favored different cells. For instance, nickel complex NT was shown to be active against PC-3 cells although its Schiff base ligand TT was unable to inhibit the growth of the same cell type. On the contrary, the inhibitory strength of both TE and TP against prostate cancer LNCaP was muted upon complexation with nickel ion. Apart from that, it is noteworthy that all compounds are less toxic towards human normal colon cell CCD-18Co compared to that of cisplatin, as the IC50 values of these compounds were failed to be determined within the tested concentration (0.1 - 30.0 μg/mL). This may be an indication of selectivity towards cancerous cells, which is lacking in cisplatin. Interactions with DNA were evaluated via UV-Vis spectrophotometry and the result suggested non-intercalation binding mode, because batochromic effect and/or isobestic point was absent despite hypochromism was observed. This is further confirmed with the aid of docking simulations (AutoDock 4.2), where all the compounds tested were suggested to interact with the minor groove of DNA. Furthermore, both methods have generated binding constant and estimated binding energy of similar order, with NE being the strongest DNA-binding agent. Increased expression of topoisomerase I was observed in numerous neoplastic tissues, particularly due to its importance in replication of DNA and ultimately the proliferation of the cells. Despite its importance in cancerous cells (such as colon cancer), topoisomerase I, the common target in cancer treatment (especially colon cancer), is not inhibited by any of the synthesized compounds. In conclusion, the results suggested the compounds synthesized, which are DNA binders, exert their cytotoxic effects against the prostate and colon cancer cells tested in a topoisomerase I-independent manner.